24-HOUR NIGHT-DAY BLOOD PRESSURE AND WAVE REFLECTIONS PATTERNS IN HEART TRANSPLANT AND HYPERTENSIVE INDIVIDUALS. (June 2018) - Maloberti, A.; Masciocco, G.; Varrenti, M.; Meani, P.; Protogerou, A.D.; Argyris, A.; Weber, T.; Pecnik, P.; Sharman, J.; Wassertheurer, S.; Hametner, B.; Frigerio, M.; et al.
Abstract : Objective: Heart denervation, a consequences of cardiac transplantation, results in increased resting heart rate (HR) with impact on blood pressure (BP) and on its 24hr pattern. A higher prevalence of non-dipping phenomenon has been reported in heart transplant recipients (HTX), but a specific analysis of night-day BP phenotypes is still lacking particularly regarding central hemodynamics. Aim of this study was to investigate 24hr changes of brachial and central BP, but also of 24 h steady state (stroke volume-SV, cardiac output-CO, peripheral resistance-PR) and pulsatile (antegrade and reflected waves) hemodynamics in HTX recipients, comparing them to treated hypertensivs. Design and method: We enrolled 25 HTX recipients and 25 hypertensives matched by age, sex and 24hr brachial BP. Ambulatory 24 h brachial and central BP, parameter were assessed with brachial oscillometry (Mobil-o-graph) and dedicated software for waveform analysis (ARCSolver). Results: The two groups were well matched for age (58.5 ± 12.1 vs 58.5 ± 12.2 years, p = 0.9), sex (females 20% for group) and brachial and central 24hr BP (125/82 ± 11/8 vs 127/81 ± 11/9mmHg, p = ns). Mean time after HTX was 10.1 ± 9.5 years; and this group presented with higher 24hr (79.5 ± 10.3 vs 71.4 ± 8.3bpm) and daytime HR (82.7 ± 11.4 vs 74.4 ± 8.5 bpm, p < 0.05 for both) compared to hypertensives. In both groups there were significant day/night decreases in systolic, diastolic and mean peripheral and central BP, as well as HR. In hypertensives CO decreased during nighttime, and PR remained constant. Due to the decrease in HR, SV increased, with a parallel increase in antegrade and a more pronounced increase in reflected waves. In HTX, PR decreased during nighttime, accompanied by an increase in SV and a stable CO. In turn, changes in wave reflections were less pronounced during nighttime. Conclusions: In treated hypertensives, the day-night pattern consists of a BP decrease with changes in wave reflections that increase during the night and are related to HR decrease, but also to postural and PR changes. In HTX, differences are observed regarding CO, PR and wave reflections. Differences are probably related to heart denervation and autonomic nervous system relative changes but further studies are needed.